Perlindungan Hukum Konsumen Terhadap Label Produk Jamu (Studi Pasar Jamu Nguter) - Firmansyah, Fendi; , Dr. Kelik wardiono, SH., M.H (2016)
This research is aimed to describe profil of jamu's label and legal protection for jamu's consumer against regulation for jamu labelling. Label is a piece material attached to a container or product, on which is written or printed information about the product. From these definition, can be cocluded label contains information. TheRight for reliable information is one of customer's right. On the contrary there are still many problems for labeling especially for jamu's label which do not get much attention from the customer and distributor, even though label is important for customer's protection. Research method for this research is using doctrinal approach. The type of research used is descriptive research. Descriptive research describe the legal protection for jamu's consumer against label regulation. The writer used normative approach for the data analysis. From the result of the research above, it can be concluded labeling regulation among the inspected jamu there are few jamu's product that did not meet the legal requirement.